GAMBARAN KUALITAS AIR SUNGAI SAMBAS DAN DANAU KURAPAN DESA SEPANTAI KABUPATEN SAMBAS - Agam, Beryaldi; Yunita, Nurul Fatimah; Atmajaya, Onesimus Dhyas Dwi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2021)
Community service programs (PKM) by independent funding has done because of the sudden death of many fish due to the effect of environmental pollutions in the river of Sambas at 2019. Decrease of water quality as the effect of human activity like agriculture, palm plantation, fisheries, mining, and the industries around Sambas treams is an impact of the water quality decrease. From that phenomena needs service program with a counceling methods about water quality. The objective of this service are; 1) provide a knownledge, educational insight, skills and awareness to participate on environmental protection from destructive activity, 3) provide a training about mechanism and procedure of water quality measuring, and water quality sampling to test at laboratory. There are two activity on this program, that is socialization with a presentation materials and focus group discussions (FGD) and water quality sampling training with material exposure then carried out direct practice to measuring any water quality parameters that will test at laboratory. This independent programs implemented in Sepantai Village Sejangkung at the District of Sambas on September 12 – 13, 2020. There are 25 participants attended on this event, 15 participants are come from local society and Village Aparattus from Sepantai Village.Keywords: Pollutions, training, water quality, river, environtment